2013
DOI: 10.1682/jrrd.2012.11.0206
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D deficiency, secondary hyperparathyroidism, and heterotopic ossification in spinal cord injury

Abstract: Abstract-Our objective was to explore the relationship between low vitamin D, secondary hyperparathyroidism, and heterotopic ossification (HO) in patients with spinal cord injury (SCI). Ninety-six subjects with acute or chronic motor complete SCI participated. Levels of serum vitamin D25(OH), calcium, and intact parathyroid hormone (PTH) were collected, and information regarding nutritional patterns and fracture history was obtained from subjects. Evidence of current or previous HO was ascertained through char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…In one study [39], over 80% of the participants remained insufficient after vitamin D supplementation with 2000 IU daily over a two-week period. Similar findings were shown with a supplementation of 800 IU daily over a duration of one year [39], and in a study where the compliance for taking vitamin D supplements was only at 72% [40]. Our study showed not only a high compliance but also that a dosage of 6000 IU vitamin D daily over six weeks would be sufficient to increase vitamin D status to a normal level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In one study [39], over 80% of the participants remained insufficient after vitamin D supplementation with 2000 IU daily over a two-week period. Similar findings were shown with a supplementation of 800 IU daily over a duration of one year [39], and in a study where the compliance for taking vitamin D supplements was only at 72% [40]. Our study showed not only a high compliance but also that a dosage of 6000 IU vitamin D daily over six weeks would be sufficient to increase vitamin D status to a normal level.…”
Section: Discussionsupporting
confidence: 89%
“…Most of these studies failed to achieve a sufficient vitamin D status after the supplementation period [39,40]. In one study [39], over 80% of the participants remained insufficient after vitamin D supplementation with 2000 IU daily over a two-week period.…”
Section: Discussionmentioning
confidence: 99%
“…Oleson et al, 19 also reported their observations well in resonance to the present study. Gaspar AP et al 20 and Bauman WA et al, 16 observed that serum 25(OH)D level was positively correlated with the lumbar spine T score.…”
Section: Resultssupporting
confidence: 91%
“…In the study of HO in spinal cord injury, 12 of the 96 subjects developed HO.12 Nine of these 12 had secondary hyperparathyroidism, with levels ranging from 72 to 169 pg/mL. A proposed mechanism is that parathyroid hormone (PTH) enhances BMP activity in premature osteoblasts which can lead to HO [12], [13]. A clinical review of literature done in 2013 states that twenty percent of spinal cord injuries exhibit HO afterwards.…”
Section: Discussionmentioning
confidence: 99%